Effect of ethanol perturbation on viscosity and permeability of an inner membrane in Bacillus subtilis spores. - Loison,P; Gervais,P; Perrier-Cornet,JM; Kuimova,MK (Biochimica et Biophysica Acta, 2016)
In this work, we investigated how a combination of ethanol and high temperature (70°C), affect the properties of the inner membrane of Bacillus subtilis spores. We observed membrane permeabilization for ethanol concentrations ≥50%, as indicated by the staining of the spores' DNA by the cell impermeable dye Propidium Iodide. The loss of membrane integrity was also confirmed by a decrease in the peak corresponding to dipicolinic acid using infrared spectroscopy. Finally, the spore refractivity (as measured by phase contrast microscopy) was decreased after the ethanol-heat treatment, suggesting a partial rehydration of the protoplast. Previously we have used fluorescent lifetime imaging microscopy (FLIM) combined with the fluorescent molecular rotor Bodipy-C12 to study the microscopic viscosity in the inner membrane of B. subtilis spores, and showed that at normal conditions it is characterized by a very high viscosity. Here we demonstrate that the ethanol/high temperature treatment led to a decrease of the viscosity of the inner membrane, from 1000cP to 860cP for wild type spores at 50% of ethanol. Altogether, our present work confirms the deleterious effect of ethanol on the structure of B. subtilis spores, as well as demonstrates the ability of FLIM - Bodipy-C12 to measure changes in the microviscosity of the spores upon perturbation.